ΤΑ ΓΕΝΕΑΛΟΓΙΚΑ ΔΕΝΤΡΑ ΤΟΥ ΑΡΧΕΙΟΥ ΤΗΣ ΚΑΘΟΛΙΚΗΣ ΑΡΧΙΕΠΙΣΚΟΠΗΣ ΤΗΣ ΣΑΝΤΟΡΙΝΗΣ - ΣΤΕΦΑΝΙΔΟΥ ΑΛΕΞΑΝΔΡΑ (Eoa kai Esperia, 2003)
The family trees of Santorine found in the archives of the Catholic Archdioceseof Santorine constitute research tools for the history of the social web existingduring the island’s Roman Catholic era as well as in recent times. The starting pointof the family trees is focused on the period between the 15th and the 18th century.On the basis of the family trees it becomes clear that there are families of Italian,French and Spanish origin. The family trees provide information on the professionsheld by some members. Regarding the social and demographic situation, informationis provided on members of families who died young as well as those membersbelonging to the noble class. The reason for compiling the family trees is mentionedin the title accompanying them per il Legato Pio, that is to say to safeguard a certainecclesiastical legacy. In the Report of the Roman Catholic Bishop de Cigalla of1830 it is stated that the Legati PU of the families of Santorine safeguard the juspatronatus. As regards the use of the family trees as tools to study the archives ofthe Catholic Archdiocese of Santorine, extensive reference is made to the Syrigon-Vassalon family tree.